Modulatory role of Magnesium and Copper Sulphates on Serum Lipid profile and Serum Liver Enzymes in Fructose-induced Diabetic Wistar Rats - Tanko Y, Alhassan M, Mohammed K. A, Eze E.D, Jimoh A, Sada N. M, Muhammad A and Mohammed A (Journal of Applied Pharmaceutical Science, 2013)
The aim of this study is to determine the effect of magnesium and copper sulphates on serum lipid profile and serum liver enzymes in fructose-induced diabetic Wistar rats. Diabetes was induced by administration of 20% (20g/100ml) of fructose dissolved in distilled water and administered to the animals for a period of six (6) weeks. After which the animals were randomly assigned into 4 groups of 6 rats each. Group I served as diabetic negative control were administered 1ml distilled water. Group II were administered Magnesium sulphate (250 mg/kg b w). Group III were administered Copper sulphate (250 mg/kg b w) and Group IV administered Metformin (250 mg/kg b w) served as positive control. All treatments were given orally for a period of seven days. The results obtained showed a statistically significant decrease (p
Keywords: Diabetes, magnesium sulphate, copper sulphate, lipid